An Examination of the Relationship between Leader-Member Exchange and Innovative Work Behavior with the Moderating Role of Trust in Leader: A Study in the Turkish Context - BÜLBÜL, SEÇİL (ELSEVIER SCIENCE BV, 2015)
This study aimed to examine the influence of leader-member exchange (LMX) from the perspectives of subordinates on innovative work behavior (IWB) and to test the role of perceived trust in leader as a moderator variable. A structured research survey was performed and data were collected from a sample of 327 non-supervisory employees that represented corporations and medium size companies from different sectors operated in Turkey. Confirmatory Factor Analysis (CFA) was used to examine the construction of the questionnaire and the relationship among LMX, IWB and trust in leader were tested applying the Structural Equation Modelling (SEM) technique. The analysis indicated that LMX quality had positive influence on trust in leader, but the influence of LMX was not significant on employees' IWB. Contrary to what was hypothesized, LMX did not influence IWB. Moreover, the results revealed that trust in leader had positive influence on IWB and significantly moderated the relationship between perceived LMX quality and IWB of employees. Key implications of the research findings both for theory and for practice were discussed, potential limitations were identified, and suggestions for future research were specified.
Keywords: Leader-Member Exchange; Innovative Work Behavior; Trust in Leader; Structural Equation Modelling (SEM; PERCEIVED ORGANIZATIONAL SUPPORT; SOCIAL-EXCHANGE; MEDIATING ROLE; INDIVIDUAL INNOVATION; EMPLOYEE CREATIVITY; INTEGRATIVE MODEL; SELF-LEADERSHIP; PERFORMANCE; PERCEPTIONS; QUALITY